Physical Mapping of Chromosomes Using Unique Probes - Alizadch, Farid; Karp, Richard M.; Weisser, Deborah K.; Zweig, Geoffrey (1994)
In this paper we present several combinatorial algorithms for reconstructing a DNA strand given a collection of overlapping fragments of the strand. A human chromosome, which is a DNA molecule of about lo*base pairs, is too long to be studied in its entirety and must be broken into fragments or clones. Depending on the cloning technology used, the sizes of the clones may be as small as 3,000 base pairs or as large as 2,000,OOO base pairs. Information is gathered from the individual clones, and then the DNA is reconstructed by mathematically determining the positions of the clones.
Ubiquity